delectable desserts : over 75 spectacular recipes for delicious desserts photographed step-by-step - Fraser, Linda, editor 415899 (London : Hermes House, 2003)
Indulge your fantasies with this superb collection of mouthwatering desserts. Recipes include Sticky Toffee Pudding, Crame Caramel and Boston Banoffee Pie, as well as more extravagant indulgencias including Zabaglione, Blackberry and Apple Romanoff, and Rasperry Meringue Gateau. Over 75 spectacular recipes for delicious desserts of all kinds, from ice creams, bombes and mousses to tempting souffl?s, pies and tarts. Over 300 photographs, highlighting each step-by-step recipe and the finished dish. Ideas suitable for all occasions - from special events and celebrations to informal entertaining and everydayfamily meals and treats. Includes quick, healthy, low-fat low-cholesterol recipes as well as rich traditional desserts. Information on basic techniques, with professional cook's tips and hints throughout.